ChemInform Abstract: Iodine‐Mediated Thiolation of Phenol/Phenylamine Derivatives and Sodium Arylsulfinates in Neat Water. Issue 18 (April 2016) - Wang, Dingyi; Zhang, Rongxing; Lin, Sen; Yan, Zhaohua; Guo, Shengmei
Abstract: An iodine‐mediated thiolation of phenols, naphtols, or anilines with benzenesulfinates in water provides the corresponding aromatic thioethers under environment‐friendly conditions.